1993
DOI: 10.1111/j.1559-1816.1993.tb01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Task Performance as a Function of Type of Feedback: Learning‐Oriented Versus Performance‐Oriented Feedback1

Abstract: A laboratory study was conducted to examine the effects of learning‐oriented versus performance‐oriented feedback of task performance. The research also examined the role of self‐efficacy as a moderator. Subjects were college students participating for course credit. The task involved using a computerized simulation of the Space Shuttle's Remote Manipulation System (RMS). Results provided evidence of the beneficial effects of learning‐oriented feedback on performance for the performance dimension addressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…Based on these preliminary data, we assert that process-oriented PW contribute to cognitive schema construction during the execution of (complex) subtasks, that process-oriented SAPs are helpful in following a metacognitive strategy during task execution, and that productoriented WOE are of most value for understanding task exection afterward. Our students reported that the presence of both process-and outcomeoriented cueing has led to better performances (pleas) and more focused information searching (while preparing the plea), as was found earlier (e.g., Earley, Northcraft, Lee, & Lituchy, 1990;Johnson, Perlow, & Pieper, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…Based on these preliminary data, we assert that process-oriented PW contribute to cognitive schema construction during the execution of (complex) subtasks, that process-oriented SAPs are helpful in following a metacognitive strategy during task execution, and that productoriented WOE are of most value for understanding task exection afterward. Our students reported that the presence of both process-and outcomeoriented cueing has led to better performances (pleas) and more focused information searching (while preparing the plea), as was found earlier (e.g., Earley, Northcraft, Lee, & Lituchy, 1990;Johnson, Perlow, & Pieper, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…Outcome feedback -also called performance-oriented feedback -provides participants with the knowledge of their results. While it is posited that such form of outcome would allow the individual to improve his or her performance by altering the strategies used to implement the task, some studies suggest that outcome feedback is ineffective for complex, uncertain tasks (Jacoby et al 1984;Johnson et al 1993).…”
Section: Level 4: Presentationmentioning
confidence: 99%
“…Feedback provides the ability to reflect on the educational experience to enhance learning (Salas et al 2005;Fanning & Gaba 2007). Studies of feedback in medicine, also in fields such as psychology and management, have shown that specific feedback has a better potential of improving performance than vague or no feedback, because it increases knowledge about performance (Johnson et al 1993;Hewson & Little 1998), and, when no goals exist, allows the learner to set specific goals for learning (Ilgen et al 1979;Early et al 1990). These goals in turn enhance performance by increasing motivation, effort, and persistence, and by improving the way strategies for success are devised (Locke et al 1981;Early et al 1990).…”
Section: Level 4: Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…These existing studies indicate benefits of delayed feedback for the learning of tasks that involve strategic planning and processing. More generally, the learning of effective task strategies has been found to be best supported by process-oriented feedback that focuses on the underlying solution processes, rather than specific outcomes of solution attempts (Butler 1987;Earley, Northcraft, Lee, & Lituchy, 1990;Johnson, Perlow, & Pieper, 1993).…”
Section: Delayed Feedbackmentioning
confidence: 99%